2015
DOI: 10.1016/j.scr.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous resident c-Kit cardiac stem cells increase in mice with an exercise-induced, physiologically hypertrophied heart

Abstract: Physical activity evokes well-known adaptations in the cardiovascular system. Although exercise training induces cardiac remodeling, whether multipotent stem cells play a functional role in the hypertrophic process remains unknown. To evaluate this possibility, C57BL/6 mice were subjected to swimming training aimed at achieving cardiac hypertrophy, which was morphologically and electrocardiographically characterized. Subsequently, c-Kit(+)Lin(-) and Sca-1(+)Lin(-) cardiac stem cells (CSCs) were quantified usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 50 publications
2
16
0
1
Order By: Relevance
“…With ageing, we observed a depletion of CVPC population, consistent with the decrease of the progenitor cells in dystrophin-deficient skeletal muscle [ 20 ]. Therefore, although CVPCs and satellite cells have different functions, our findings likely reveal a common phenomenon involving an early-stage recruitment triggered by cardiac injury as also previously shown [ 34 , 52 ], but followed by rapid depletion of the CVPC pool. We summarize our findings and a proposed mechanism of the CVPC in the dystrophin-deficient heart in the diagram of Figure 7 .…”
Section: Discussionsupporting
confidence: 79%
“…With ageing, we observed a depletion of CVPC population, consistent with the decrease of the progenitor cells in dystrophin-deficient skeletal muscle [ 20 ]. Therefore, although CVPCs and satellite cells have different functions, our findings likely reveal a common phenomenon involving an early-stage recruitment triggered by cardiac injury as also previously shown [ 34 , 52 ], but followed by rapid depletion of the CVPC pool. We summarize our findings and a proposed mechanism of the CVPC in the dystrophin-deficient heart in the diagram of Figure 7 .…”
Section: Discussionsupporting
confidence: 79%
“…Although the principal player of cardiac hypertrophy is the enlargement of differentiated cardiomyocytes, Leite et al [102] recently demonstrated that also c-kit + cardiac stem cells (CSC) participate to cardiac hypertrophy generated by physical exercise. c-Kit + CSC have been first reviewed 10 years ago [103].…”
Section: Heart Stem Cells and Physical Activitymentioning
confidence: 99%
“…CSCs include, among others, c-kit + Lin − and Sca-1 + -Lin − cells, Isl-1 progenitors, epicardial progenitors, and progenitors generating cardiospheres and muscle-derived mesenchymal stem cells. Experimental studies have shown that it is mostly c-kit + Lin − cells that seem to increase in the heart in response to exercise training [ 5 ]. However, it has been speculated that Sca-1 + -Lin − might also be stimulated in physiological hypertrophy.…”
Section: Physiological and Pathological Myocardial Hypertrophymentioning
confidence: 99%